Acute Dependency Reaction to Meperidine: A case report - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2010)
Postoperative discitis is a rare and painful complication that may emerge following spine procedures. We present a 34-year-old male patient with postoperative discitis who had been addicted to meperidine during pain relief. Three weeks after routine lumbar discectomy, this patient presented with clinical findings and radiographic imaging consistent with discitis. Meperidine, rate of administration was 1 mg/kg three times a day, was prescribed for his low back pain. After two weeks of opioid therapy an iatrogenic meperidine addiction occurred. Opioid analgesics are helpful for excessive painful conditions as a discitis. Although this case showed us we should be careful when we prescribe opioids.
Keywords: Discitis; meperidine; low back pain; pain relief; BACK-PAIN; PREVALENCE